Life cycle costing - Muthu, Subramanian Senthilkannan (Environmental footprints and eco-design of products and processes,, 2023)
Life Cycle Costing (LCC) is a well-known and popular method to evaluate the economic sustainability, which as the term implies is structured on the life cycle of a product or process. LCC is a method primarily consisting of estimating the total cost of a product, taking into account the whole life cycle of the product as well as the direct and external costs. It is one of the important methods and tools under the sustainability umbrella. This book describes the concept of LCC and offers several interesting case studies.